Effect of IBA, time of layering and rooting media on air-layers and plantlets survival under different growing nursery conditions in guava - Rymbai, H.; Reddy, G. Sathyanarayana (Indian Journal of Horticulture, 2010)
The present investigation on the effect of IBA concentrations, time of layering and rooting media on rooting, root characters and survival percentage of rooted air layers under different growing nursery conditions i.e open and polyhouse conditions on guava, cv. L-49 were carried out during 2008-09. Three different concentration of IBA viz., 2000, 3000 and 4000 ppm were used in three time of layering viz., 15th June, 15th July and 15th August with two rooting media viz., sphagnum moss and coco peat. It was revealed that High percentage of rooting and root characters of air layers of guava have been successfully achieved by exogenous application of IBA at 4000 ppm. Regarding the time of layering, 15th August gave the maximum rooting success and root attributes. Among the rooting media, moist sphagnum moss produced highest rooting percentage and root characters. The survival of rooted air layers was found to be maximum with the treatment combination of IBA at 4000 ppm, 15th August and sphagnum moss and polyhouse conditions produced higher survival than open conditions after 45 days of detachment from the mother plants.